Ionosphere over Ukrainian Antarctic Akademik Vernadsky station under minima of solar and magnetic activities, and daily insolation: case study for June 2019 - Bogomaz, O. V.; Shulha, M. O.; Kotov, D. V.; Zhivolup, T. G.; Koloskov, A. V.; Zalizovski, A. V.; Kashcheyev, S. B.; Reznychenko, A. I.; Hairston, M. R.; Truhlik, V. (Ukrainian Antarctic Journal, 2019)
We present ionospheric observational results obtained over Ukrainian Antarctic Akademik Vernadsky station. Ionospheric parameters (peak electron density and height, electron density and electron and ion temperatures in the topside) during the period near the local winter solstice in the Southern Hemisphere (June 28—29, 2019) are considered. The main objective is to show distinctive features of variations in ionospheric parameters during a prolonged period with very low solar and magnetic activities, and minimal daily insolation. Methods. F2 layer peak electron density and height were calculated from ionograms obtained with ionosonde installed at the station with subsequent profile inversion. Defense Meteorological Satellite Program (DMSP) and Swarm data acquired over the station are used as well. Diurnal variations of electron density, and electron and ion temperatures at the altitude of the satellites’ orbits were calculated using a set of sub-models of the International Reference Ionosphere-2016 (IRI-2016) model. Results. We found a very good agreement between the observed and model variations of F2 layer peak electron density. Significant (by 2 times) nighttime enhancement of electron density was observed on June 29. Electron density models show the similar increase of the density at the same time interval but this enhancement is much more smoothed comparing with the observations. Peak height values obtained using ionosonde are very close to ones calculated with the IRI-2016 sub-models. Satellite data are in a good consistency with the IRI model predictions, especially for electron density obtained by Swarm satellite. Conclusions. Multi-instrumental observations revealed a number of unique features of the ionosphere over Antarctic Peninsula under minima of solar and magnetic activities, and daily insolation.